Community-based participatory research (CBPR) approach to study children’s health in China: Experiences and reflections - Liu, Jianghong (Int J Nurs Stud, 2011)
BACKGROUND: Community-based participatory research principles have been successfully applied to public health research in U.S. settings. While there is a long history of collaboration between government and communities in China, to date, community-based participatory research has not been used in children’s environmental health studies. METHOD: This article describes how community-based participatory research principles were applied by an international research group to the China Jintan Child Cohort Study, a longitudinal study of malnutrition and lead exposure on cognitive and neurobehavioral development. Challenges emerged and lessons learned from implementing the study were discussed and recommendations were presented. CONCLUSION: We conclude that the community-based participatory research model can be applied in conducting and promoting environmental health research in China and researchers should be prepared for special challenges and cultural constraints in the implementation of the research in regards to human subject regulations, information dissemination, and culture.